Analysis of the Influence of Behavioral Aspects on Cost Control (Case Study at PT Ceweng Connection Dander Bojonegoro) - Ferdiyanto, Jaya; Trisnaningsih, Sri (PT FORMOSA CENDEKIA GLOBAL, 2024)
The purpose of this research is to find out whether PT Ceweng Connection's cost management is influenced by behavioral factors. The population of this research are workers at PT Ceweng Connection. Qualitative terminology is the research approach used in this research. These findings indicate that there are behavioral factors that influence cost management in a profitable and statistically meaningful way in companies. The reason is because the organization prioritizes a culture of good behavior. Therefore, workers are expected to be able to follow standard operating processes and procedures (Standard Operating Procedures) using a positive attitude and follow all company protocols in carrying out assigned work without hesitation, to ensure that no emotional conflicts arise again at PT Ceweng Connection Dander.